A case of periorbital necrotizing fasciitis rapidly progressing to severe multiorgan failure. Issue 4 (30th April 2018) - Eiben, Paola; Rodriguez-Villar, Sancho
Abstract: Periorbital necrotizing fasciitis (PNF) is a severe suppurative infection of the subcutaneous tissue and underlying fascia of the periorbital region. Typically, the course of PNF is milder and has a better prognosis than that of necrotizing fasciitis in other parts of the body. As such, this disease is thought to be associated with a significantly smaller risk of morbidity and mortality. Nevertheless, it is a rare and devastating condition that can lead to disfigurement, blindness and death. Early recognition is critical to improved patient outcomes. Here, we describe a case of PNF in a 60-year-old male that rapidly progressed to widespread systemic involvement and severe multiorgan failure requiring ventilatory, cardiovascular and renal support. Treatment included broad-spectrum antibiotics, intravenous immunoglobulin and surgical debridement. This case highlights the life-threatening nature of PNF, as demonstrated by rapid progression to multiorgan dysfunction and the need of an urgent surgical intervention.